The Ease of Form Completion Influences the Intention to Report Patient Safety Incidents - Nuraeni, Neli; Kusumapradja, Rokiah; Mulyani, Erry Yudhya; Pamungkas, Rian Adi; Ruswanti, Endang (Syntax Literate, 2025)
This study aims to analyze the influence of positive attitude (X1), social support (X2), and ease of form completion (X3) on Patient Safety Incident (PSI) reporting behavior (Y), with reporting intention (Z) as a mediating variable. Using a causal associative approach with a cross-sectional design, data were collected through questionnaires from 150 inpatient nurses selected via purposive sampling. Structural Equation Modeling (SEM) was employed to examine variable relationships. Key findings reveal: (1) positive attitude, social support, and ease of form completion significantly affect both reporting intention and PSI reporting behavior; (2) reporting intention partially mediates the relationship between the three independent variables and reporting behavior; (3) social support and ease of form completion exhibit the strongest direct effects on reporting behavior. The study highlights that strengthening patient safety culture requires integrating psychological (attitude), social (support), and technical (system usability) factors. Practical implications suggest hospital management should develop policies fostering positive attitudes through training, enhance social support via team collaboration, and streamline technology-based PSI reporting systems. These measures are expected to improve reporting transparency and accuracy, ultimately advancing patient safety service quality.